2005
DOI: 10.1103/physrevlett.94.097202
|View full text |Cite
|
Sign up to set email alerts
|

Weak Charge-Lattice Coupling Requires Reinterpretation of Stripes of Charge Order inLa1xCax

Abstract: Modulations in manganites attributed to stripes of charge/orbital/spin order are thought to result from strong electron-lattice interactions that lock the superlattice and parent lattice periodicities. Surprisingly in La1-xCaxMnO3 (x>0.5,90 K), convergent beam (3.6 nm spot) electron diffraction patterns rule out charge stacking faults and indicate a superlattice with uniform periodicity. Moreover, large area electron diffraction peaks are sharper than simulations with stacking faults. Since the electron-lattic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
3
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 36 publications
6
82
3
3
Order By: Relevance
“…This result is in contrast with the belief at the early stage of the research of the CO-OO phenomena, but in accord with the recent results 16,17,18,19,20,21,22,23,24,25 . This indicates that various interactions, such as electron-lattice, Coulomb repulsion, and magnetic interactions, should be taken into account to correctly understand the nature of chargeordered state.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This result is in contrast with the belief at the early stage of the research of the CO-OO phenomena, but in accord with the recent results 16,17,18,19,20,21,22,23,24,25 . This indicates that various interactions, such as electron-lattice, Coulomb repulsion, and magnetic interactions, should be taken into account to correctly understand the nature of chargeordered state.…”
Section: Discussioncontrasting
confidence: 57%
“…Many diffraction and theoretical studies have reported the checkerboard type charge order of Mn 3+ and Mn 4+ ions with charge disproportionation and stripe-type orbital order, explaining a complex antiferromagnetic spin order at low temperatures in half-doped manganites 7,8,9,10,11,12,13,14,15,16 . On the other hand, another model with less distinct charge disproportionation has also been proposed 17,18,19,20,21,22,23,24,25 . For example, taking into account the on-site Coulomb interaction, Brink et al have suggested 17 that maximum value of charge disproportionation is as little as 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Increased trapping potential reduces T C and increases the strength of CM R. This mechanism is supposed to exp lain the decrease in ferro magnetic transition temperatures and increased magnetoresistance going from La 0.7 Sr 0.3 MnO 3 (T C =355 K) to La 0.75 Ca 0.25 MnO 3 (T C =240 K) and La 1.2 Sr 1.8 Mn 2 O 7 (T C =120 K). On the other hand, the picture of strong electron-lattice interaction has been questioned for thin films of La 1-x Ca x MnO 3 , x ≥ 0.5 [10]. We used neutron scattering to measure temperaturedependence of 2 in La 0.7 Sr 0.3 MnO 3 in order to investigate the relationship between U 2 and the electrical resistivity known fro m the literature.…”
mentioning
confidence: 99%
“…20 However, in a more recent electron diffraction study this conventional interpretation was claimed to be insufficient. 17 In LCMO x = 0.52 the charge modulation was found to be uniform and to have a non-integer periodicity even by reducing the electron spot size to 3.6 nm, which is below the expected stacking fault distance implanted into the hypothesized q = 0.5·a* Mn 3+ /Mn 4+ plane stacking by doping to x = 0.52 (Fig.1d). The authors in this study (Ref.17) assumed that these unconventional charge modulations arise solely from the cationic valence electron structure, and in consequence, they claimed that the localised Mn 3+ /Mn 4+ plane stacking or stripe models may be insufficient to explain these findings.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 This new view of CO mechanisms developed from findings of commensurate and incommensurate charge periodicities in CO LCMO at x ≥ 0.5, [16][17][18] and a weak commensurate phase for x < 0.5. 19 The periodicities of such charge modulations (along the a crystallographic orientation) were shown to differ from the original lattice periodicity and the modulation wave vector q was found to be correlated to the doping level x below the CO transition temperature T CO by q ≈ (1-x)·a*, where a* is the reciprocal space vector of the parent orthorhombic Pnma unit cell.…”
Section: Introductionmentioning
confidence: 99%